A Chronic Disease Management Program at the Rowan School of Osteopathic Medicineâ€™s Student-Run Free Clinic - Eric Goldwaser; Bernadette Bibber; Kathryn Eckert; Samantha Paglinco; Kyley Leroy; Danielle Alaimo (Journal of Student-Run Clinics, 2016)
In the United States, one out of every four adults is living with at least one chronic disease. Treatment of these chronic conditions accounts for 84% of healthcare spending. Successful treatment of chronic diseases involves support from family, the community, and the healthcare system. In this descriptive report, we outline the beginning steps of implementing a new program aimed at addressing a pervasive chronic disease in the population seen at our student-run clinic. The Rowan University School of Osteopathic Medicineâ€™s Camden Community Health Center in conjunction with the Camden Area Health Education Center gathered information from a community needs assessment and focus group to better direct efforts at optimizing healthcare delivery to the priorities of the community. After collecting the data, a chronic disease management pilot program targeting patients with chronic hypertension was created. The program included a course run over a six-week period, in which a peer-run educational group focused on lifestyle changes and medical management of hypertension. This plan utilized community health workers, a â€œbuddy system,â€ and family support. At the end of the program, participants were provided with a weekly blood pressure log, action plan for their disease management, and specific follow-up appointments. Furthermore, we briefly share preliminary data that allowed us to gauge success of the pilot program and form the basis for a larger, more comprehensive follow-up study.